Evaluation of the effect of intravenous nitroglycerine on short-term survival of patients with acute heart failure according to congestion and perfusion status at emergency department arrival. (20th July 2022) - Miró, Òscar; Espinosa, Begoña; Gil, Víctor; Jacob, Javier; Alquézar-Arbé, Aitor; Masip, Josep; Llauger, Lluís; Tost, Josep; Andueza, Juan Antonio; Garrido, José Manuel; Mojarro, Enrique Martín; Urbano, Carmen Agüera; et al.
Abstract : Objectives: We investigated if the phenotypic classification of acute heart failure (AHF) based on the number of signs/symptoms of congestion and hypoperfusion at emergency department (ED) arrival identifies subgroups in which intravenous (IV) nitroglycerine (NTG) use improves short-term survival. Methods: We included consecutive AHF patients diagnosed in 45 Spanish EDs, who were grouped according to phenotype severity. The main outcome was 30-day all-cause death. Propensity scores (PS) for NTG use were generated using variables associated with death. Analysis of interaction was performed in subgroups of patients based on congestion, hypoperfusion, age, sex, coronary artery disease (CAD), left ventricular ejection fraction (LVEF) and SBP. Results: We analyzed 16 437 AHF patients (median = 83 years; women = 56%); 1882 received NTG (11.4%). In the whole cohort, the cumulative 30-day mortality in patients receiving NTG was higher (11.5% vs. 9.6%; unadjusted HR, 1.19; 95% CI, 1.04–1.36), but not in the PS-matched cohorts (1698 pairs of patients; 11.5% vs. 10.5%; HR, 1.10; 95% CI, 0.90–1.35). Mortality was increased in NTG-treated patients with mild congestion (HR, 2.09; 95% CI, 1.19–3.67), especially in those without hypoperfusion (HR, 2.51; 95% CI, 1.24–5.10). Interaction analysis of the PS-matched cohorts confirmed detrimental effects of NTG use in less congested patients, whereas beneficial effects were only observed in patients with decreased LVEF (<50% subgroup: HR, 0.59; 95% CI, 0.37–0.92; ≥50% subgroup: HR, 1.30; 95% CI, 0.66–2.56; P = 0.002). Conclusion: Phenotypical classification of AHF based on congestion/hypoperfusion at ED arrival does not identify subgroups of patients in whom IV-NTG would decrease mortality, although it could potentially be beneficial in those with LVEF of less than 50%. This hypothesis will have to be confirmed in the future. Conversely, our results suggest that IV-NTG may be harmful in patients with only mild clinical congestion.